Do Middle School Science Textbook Enclose an Entity of Science Literacy? - Didit Ardianto; Indarini Dwi Pursitasari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
This study aims to analyze the middle school of science the textbook based on science literacy. We used descriptive analysis to explore the domain of science literacy at 3 middle science textbooks. Observation Sheet that contain the domain of science literacy (adopted from Chiappetta, Fillman Sethna) is used to capture the present category of science literacy (body of knowledge, way of investigating, way of thinking, and interaction of science, technology and society) in any textbook. The results showed that middle school science textbooks have not yet provide a balance between body of knowledge, way of Investigating, way of thinking, and interaction of science, technology and society. The Middle science textbooks still dominate with science as a way of knowledge. Middle School science textbook that used to support science teaching should be provide balance on all four aspects of science literacy. Therefore, The development that focusing on middle school science textbooks based on science literacy need to be implemented.